Clinical Practice Guidelines for Hepatocellular Carcinoma: The Japan Society of Hepatology 2021 version (5th JSH‐HCC Guidelines). Issue 5 (10th March 2023) - Hasegawa, Kiyoshi; Takemura, Nobuyuki; Yamashita, Tatsuya; Watadani, Takeyuki; Kaibori, Masaki; Kubo, Shoji; Shimada, Mitsuo; Nagano, Hiroaki; Hatano, Etsuro; Aikata, Hiroshi; Iijima, Hiroko; Ueshima, Kazuomi; et al.
Abstract: The fifth version of the Clinical Practice Guidelines for Hepatocellular Carcinoma was revised by the Japan Society of Hepatology, according to the methodology of evidence‐based medicine and partly to the Grading of Recommendations Assessment, Development and Evaluation system, which was published in October 2021 in Japanese. In addition to surveillance–diagnostic and treatment algorithms, a new algorithm for systemic therapy has been created, as multiple drugs for hepatocellular carcinoma can be currently selected. Here, new or revised algorithms and evidence on which the recommendations are based are described.